Design and Interface Development in Electrical Vehicle Powerline Communication - Raihany Afifa Augusta; Irwan Purnama; Angga Rusdinar (Jurnal Indonesia Sosial Teknologi, 2025)
The adoption of Electric Vehicles (EVs) is growing globally due to efficiency, technological advancements, and environmental benefits, though fossil-fueled vehicles still dominate Indonesia. Supported by government initiatives, Indonesia is transitioning to EVs, aiming for Net Zero Emissions by 2060. CAN-Bus technology is Critical to EV operation, enabling efficient communication between vehicle components. Integrating power line communication (PLC) with CAN-Bus, using existing electrical grids, enhances real-time monitoring and control, and companies like Continental Engineering Services are advancing gateway technologies for EV and charging station communication. This research proposes developing an Electrical Vehicle Power Line Communication (EVPLC) system to bridge this communication gap, supporting Indonesia's clean energy goals and EV adoption. Additionally, the project emphasizes the importance of effective design using Fusion 360 software and a user-friendly Human-Machine Interface (HMI) with Nextion. Combining these tools enhances the efficiency and accessibility of EV charging stations, contributing to a more robust and user-friendly EV ecosystem.